'The ethics approval took 20 months on a trial which was meant to help terminally ill cancer patients. In the end we had to send the funding back': a survey of views on human research ethics reviews. Issue 12 (11th January 2021) - Scott, Anna Mae; Chalmers, Iain; Barnett, Adrian; Stephens, Alexandre; Kolstoe, Simon E; Clark, Justin; Glasziou, Paul
Abstract : Background: We conducted a survey to identify what types of health/medical research could be exempt from research ethics reviews in Australia. Methods: We surveyed Australian health/medical researchers and Human Research Ethics Committee (HREC) members. The survey asked whether respondents had previously changed or abandoned a project anticipating difficulties obtaining ethics approval, and presented eight research scenarios, asking whether these scenarios should or should not be exempt from ethics review, and to provide (optional) comments. Qualitative data were analysed thematically; quantitative data in R. Results: We received 514 responses. Forty-three per cent of respondents to whom the question applied, reported changing projects in anticipation of obstacles from the ethics review process; 25% reported abandoning projects for this reason. Research scenarios asking professional staff to provide views in their area of expertise were most commonly exempted from ethics review (to prioritise systematic review topics 84%, on software strengths/weaknesses 85%); scenarios involving surplus samples (82%) and N-of-1 (single case) studies (76%) were most commonly required to undergo ethics review. HREC members were 26% more likely than researchers to require ethics review. Need for independent oversight, and low risk, were most frequently cited in support of decisions to require or exempt from ethics review, respectively. Conclusions: Considerable differences exist between researchers and HREC members, about when to exempt from review the research that ultimately serves the interests of patients and the public. It is widely accepted that evaluative research should be used to reduce clinical uncertainties—the same principle should apply to ethics reviews.